Tibial Sesamoidectomy: Indications and Outcomes. Issue 4 (16th October 2019) - He, Jun Kit; Christie, Matthew; Robin, Joseph; McKissack, Haley; Shah, Ashish
Category: Midfoot/Forefoot Introduction/Purpose: Tibial sesamoidectomy has been reported to be a safe and effective procedure of treating a range of sesamoid pathologies including chronic sesamoiditis and fracture nonunion. The purpose of this retrospective case series was to determine common clinical indications for tibial sesamoidectomy and to evaluate the postoperative clinical course and outcomes. Methods: A retrospective chart review was conducted on patients who had isolated tibial sesamoidectomy after failed conservative treatment from 2009 to 2018. Demographics, comorbidities, physical exam variables, operative findings, radiographic measurements including hallux valgus angle (HVA) and intermetatarsal angle (IMA), and clinical outcomes including visual analog score (VAS), Foot Function Index (FFI), and complications were gathered. Results: Twenty-six patients (13 males and 13 females) were identified who have undergone tibial sesamoidectomy with a mean age of 49.8±18.5 years. For those 21 non-ulceration patients, VAS was significantly improved from 5.27±2.41 pre-operatively to 0.91±1.14 post-operatively (p<0.01). There was no statistically significant change in IMA (8.35±1.87º to 8.29±1.79º, p=0.93) or HVA (14.94±6.82º to 14.28±7.78º, p=0.79). Postoperative FFI was obtained for 10 patients with a mean of 132.75±50.68. For those five patients who had chronic ulceration on the plantar surface of the medial metatarsal head, four had complete healing at a mean of 15.6±5.37 weeks post-operatively. There was a 17% incidence of complications including neuritis, transfer metatarsalgia, and persistent cock-up deformity. Conclusion: When utilized judiciously and with the right indications, isolated tibial sesamoidectomy is a safe procedure which can improve pain and ulcer healing. HVA and IMA remained unchanged at final follow-up.